Altered Expression of the m6A Methyltransferase METTL3 in Alzheimer’s Disease - Huang, He (eNeuro, 2020)
Cognitive impairment in Alzheimer’s disease (AD) is associated with dysregulation of the RNA and protein expression profiles in the brain. Recent studies have highlighted the importance of RNA post-transcriptional regulation (epitranscriptomics) in higher order brain functions. Specifically, N6-methyladenosine (m6A), which controls RNA stability, splicing, translation and trafficking, plays an important role in learning and memory. This raises the question of whether m6A signaling is perturbed in AD. To address this, we investigated the expression profile of known m6A-regulatory genes using a public RNA-seq dataset and identified a subset of genes which were significantly dysregulated in the human AD brain. Among these, genes encoding the m6A methyltransferase, METTL3, and a member of the m6A methyltransferase complex (MACOM), RBM15B, were downregulated and upregulated in the hippocampus, respectively. These findings were validated at the protein level using an independent cohort of postmortem human brain samples. Unexpectedly, we observed an accumulation of methyltransferase-like 3 (METTL3), but not RBM15B, in the insoluble fractions, which positively correlated with the levels of insoluble Tau protein in the postmortem human AD samples. Aberrant expression and distribution of METTL3 in the hippocampus of the AD brain may therefore represent an epitranscriptomic mechanism underlying the altered gene expression patterns associated with disease pathogenesis.